Development of Integrated Science Learning through Lesson Studies Using A Problem-Based Learning Model - Kerans, Geterudis; Ngongo, Khristoforus Palli (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2021)
Science teachers at secondary schools are required to have interdisciplinary competence to apply the integrated concept in teaching science. This is a challenge for science teachers, and not to mention the fact that many science teachers at secondary schools graduated from Physical Education, Chemistry, and Biology. This study aim: 1) to obtain an integrated science learning model based on the most appropriate problems through lesson study, to improve students' scientific work. 2) to determine the effectiveness of the integrated science learning model by using the Problem Based Learning model in improving scientific work skills and students’ activity. The research strategy used in this study is Education Research and Development. This study is qualitative research and the data analysis technique used in this research is descriptively to analyze the development of science learning and the results of student activity observations. The result of the study shows that 1) through lesson study, science teachers can share experiences and exchange ideas for solutions to various problems that are often faced in their respective schools and collectively compile lesson plans. 2) The application of the learning process planned through lesson studies with using the Problem Based Learning model improves students' scientific work skills and activeness. The conclusion of this study is the development of learning through lesson studies using a problem-based learning model can improve students’ scientific work skills and activeness.